prove that Su(SnT)=Sn(SuT)=S
Answers
Answered by
0
Answer:
y=log(logx)
Again differentiate both sides w.r.t. x
dx
dy
=
logx
1
dx
d
(logx)
dx
dy
=
logx
1
×
x
1
×1
dx
dy
=
xlogx
1
Again differentiate both sides w.r.t. x
dx
2
d
2
y
=
(xlogx)
2
xlogx(0)−1[logx+x×
x
1
]
dx
2
d
2
y
=
(xlogx)
2
−(1+logx)
Similar questions
Political Science,
1 month ago
Physics,
1 month ago
Science,
1 month ago
Science,
3 months ago
English,
3 months ago
Accountancy,
11 months ago
English,
11 months ago
English,
11 months ago